Lymphopenia is an important prognostic factor in peripheral T-cell lymphoma (NOS) treated with anthracycline-containing chemotherapy - Jeong Seong Hyun; Eom Hyeon Seok; Lee Hye Won; Kim Won Seog; Kim Seok Jin; Jung Hyun Ae; Kim Soo Jeong; Kim Jin Seok; Kim Yu Ri; Park Joon Seong; Cheong June-Won; Min Yoo Hong (Journal of Hematology & Oncology, 2011)
Abstract Background Peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) is a heterogeneous group of aggressive T-cell lymphomas with poor treatment outcomes. The aim of this study was to evaluate whether lymphopenia at diagnosis would have an adverse effect on survival in patients with PTCL-NOS treated with anthracycline-containing chemotherapy. Methods A total of 118 patients with PTCL-NOS treated with anthracycline-containing chemotherapy from 4 Korean institutions were included. Results Thirty-six patients (30.5%) had a low absolute lymphocyte count (ALC, < 1.0 × 109/L) at diagnosis. Patients with lymphopenia had shorter overall survival (OS) and progression-free survival (PFS) rates compared with patients with high ALCs (P = 0.003, P = 0.012, respectively). In multivariate analysis, high-intermediate/high-risk International Prognostic Index (IPI) scores and lymphopenia were both associated with shorter OS and PFS. Treatment-related mortality was 25.0% in the low ALC group and 4.8% in the high ALC group (P = 0.003). In patients considered high-intermediate/high-risk based on IPI scores, lymphopenia was also associated with shorter OS and PFS (P = 0.002, P = 0.001, respectively). Conclusion This study suggests that lymphopenia could be an independent prognostic marker to predict unfavorable OS and PFS in patients with PTCL-NOS treated with anthracycline-containing chemotherapy and can be used to further stratify high-risk patients using IPI scores.